Проблема патологии щитовидной железы с позиций геоэкологии и геохимии; Разведка и охрана недр; № 8 - Денисова О. А.; Барановская Н. В. Наталья Владимировна; Рихванов Л. П. Леонид Петрович; Черногорюк Г. Э.; Калянов Е. В. (2011, 2011)
Заглавие с экрана